Intellectual economy as an imperative for the development of systems for ensuring the economic security of economic entities - S. O. Tulchynska; O. S. Solosich (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2023)
This article is devoted to analyzing the problems of adequate provision of economic processes intellectualization at the level of business structures and relevant state policy approaches for developing the intellectual economy in the context of ensuring economic security. First, the dynamics of the main quantitative indicators of intellectualization processes in the progressive countries of the world are analyzed. The relationship between the processes of intellectualization of economic development and the possibilities of ensuring the economic security of the business sector in martial law conditions is substantiated, which involves the direct involvement of the instrumental support of the intellectual economy in order to eliminate existing security challenges and threats. The critical problems of organizing effective processes of economic systems intellectualization at the national economy level in terms of general economic issues, as well as the consequences of the economy functioning in wartime conditions, have been identified. The key resource components of intellectual economy development, which include intellectual potential, information, knowledge, technologies, and creative potential, have been defined and given an extended description. Features of the infrastructural basis formation of effective generation, practical implementation, diffusion, and further development of the identified resource components are described. A detailed description of the key areas of management activity within entrepreneurial entities to intellectualize the main economic processes is given. Finally, a list of priority directions of state regulatory policy in the field of accelerating the intellectualization of economic systems has been formed, covering the most influential aspects of institutional and legal regulation, planning and programming of development processes, information policy, formation of knowledge infrastructure, provision of appropriate organizational and coordination support.